2020
DOI: 10.1002/jcb.29869
|View full text |Cite
|
Sign up to set email alerts
|

AML poor prognosis factor, TPD52, is associated with the maintenance of haematopoietic stem cells through regulation of cell proliferation

Abstract: Acute myeloid leukaemia (AML) is a blood cancer where undifferentiated myeloid cells are increased in the bone marrow and peripheral blood. As AML is dangerous and shows poor prognosis, many researchers categorised the relevant cytogenetic factors according to risk and prognosis. However, the specific reasons for poor cytogenetic factors remain unknown. We analysed a large data set from AML patients and found that TPD52 expression is elevated in patient groups with poor cytogenetic factors. As the amino acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Furthermore, SOCS3 knockdown is related to cell proliferation in GBM cell lines. In previous studies, we showed that several cancer-related genes are involved in vertebrate development ( Oh et al, 2020 ; Kang et al, 2021 ). In addition to our previous studies, many studies have suggested that signaling pathways in developmental stages and oncology are highly similar.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, SOCS3 knockdown is related to cell proliferation in GBM cell lines. In previous studies, we showed that several cancer-related genes are involved in vertebrate development ( Oh et al, 2020 ; Kang et al, 2021 ). In addition to our previous studies, many studies have suggested that signaling pathways in developmental stages and oncology are highly similar.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we showed poor prognosis in both LGG and GBM when SOCS3 expression was high. Many researchers have identified novel functions of cancer-related genes during development, and we have previously shown that several cancer-related genes are involved in vertebrate development ( Oh et al, 2020 ; Kang et al, 2021 ). In the present study, we found that SOCS3, a poor prognostic marker of GBM, is important for brain development in vertebrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated, and cDNA was synthesized as previously described. 16 A quantitative reverse-transcription polymerase chain reaction (qRT-PCR) was performed using PowerUP SYBR Green Master Mix (Thermo Fisher Scientific, Waltham, MA, USA). The expression level of the target gene was normalized to that of β-actin as an endogenous control.…”
Section: Methodsmentioning
confidence: 99%
“…Zebrafish embryos were cultured using E3 solution in incubators at 28°C. 16 In vitro transcription for mRNA injection For overexpression experiments, full length was cloned into the pcs2p + vector. mRNA was synthesized using an mMESSAGE mMACHINE SP6 (Invitrogen, Carlsbad, CA, USA).…”
Section: Maintenance Of Adult Zebrafish and Embryosmentioning
confidence: 99%